1968 in Canada : A Year and Its Legacies - Kirkey, Christopher John, 1962-; Holman, Andrew C. (Andrew Carl), 1965-; Hawes, Michael K., 1954- (Book collections on Project MUSE., 2021)
"The year 1968 in Canada was an extraordinary one, unlike any other in its frenetic pace of activities and their consequences for the development of a new national consciousness among Canadians. It was a year when decisions and actions, both in Canada and outside its borders, were thick and contentious, and whose effects were momentous and far-reaching. It saw the rise of Trudeaumania and the birth of the Parti Québécois; the articulation of the new nationalism in English Canada and an alternative vision for Indigenous rights and governance; a series of public hearings in the Royal Commission on the Status of Women; the establishment of the Canadian Radio and Television Commission, nation-wide Medicare and CanLit; and a striving for both a new relationship with the United States and a more independent foreign policy everywhere else. And more. Virtually no segment of Canadian life was untouched by both the turmoil and the promise of generational change."--